Syringocystadenoma Papilliferum - Pangarkar Meena; Shrivastava Alok; Bovhate S.K (Wolters Kluwer Medknow Publications, 1998)
Syringocystadenoma pappilliferum is a benign adnexal tumor with apocrine differentiation. It is derived from primary epithelial germ cells. It can occur as an isolated tumour or in association with naevus sebaceous of jadassohn. The common sites are scalp or face but rarely it can occur elsewhere. We present a case of syringocystadenoma palilliferum on the back.